The Role of Husband’s Support in Preventing Postpartum Depression: A Scoping Review - Ashifa, Ade Nurul; Herman, Herry; Hilmanto, Dany; Sutedja, Endang; Nurihsan, Juntika; Anwar, Ruswana (Majalah Kesehatan Indonesia, 2025)
Postpartum depression is a serious issue affecting mothers after childbirth and can harm both maternal mental health and child development. Hormonal declines postpartum increase vulnerability, often compounded by high stress and limited social support—especially from husbands. This study reviews nine articles from the past five years to examine how husband support maintains postpartum maternal mental health. Database searches with strict inclusion criteria and mixed-method analyses were conducted. Findings show that strong husband support—physical, emotional, and informational—reduces postpartum depression risk by more than twofold. Spousal relationship quality, maternal age, and socioeconomic conditions also influence outcomes, while insufficient husband support can affect fathers’ mental health. This study underscores the need for educating and engaging husbands during the postpartum period. These findings inform inclusive maternal mental health policies and programs, including: adoption and enforcement of routine EPDS screening as standard care (aligned with WHO recommendations and Indonesia’s Permenkes No. 21/2021 on maternal mental health services); strengthening family-centered services that actively involve husbands (partner-inclusive antenatal/postnatal classes, structured father education, couple counseling); culturally sensitive supports across socioeconomic contexts; and clear referral pathways from primary care to specialized services to ensure timely, equitable treatment for all mothers and families.